On lay mesh repair technique is a safe tension free repair for large incisional hernia (Prospective study) - Mjelee Kadhim Alkhalefa, Hussein; Jasim Hasan, Mohammed; Hasan Abdulsada Almaeni, Atheer (International Journal of Psychosocial Rehabilitation, 2023)
Incisional hernia remains a frequent complication of abdominal surgeries with a reported incidence of (10- 15)% Repair of large incisional hernia is a difficult surgical problem with short and long term complications , severity of these complications are related in part to the type of operative technique adopted. Aim of this study: to evaluate the outcome of repair of large incisional hernia with the (on lay tension free) mesh technique. Patients and Method: A prospective study that includes a 70 patients who underwent mesh repair for large incisional hernia on lay tension free polypropylene mesh with two points fixation during the period from January2007 to December 2011 in Al-Diwanyh Teaching Hospital. Complications like; hematoma, seroma, Wound infection, intestinal obstruction and enterocutaneous fistula Were recorded, the Follow up period Range from 4 to 21 month. Recurrence rate with the period of fellow up was recorded